Hazards of the Market: The Continuity and Dissolution of Interorganizational Market Relationships - Уэйн Бейкер; Роберт Фолкнер; Джин Фишер (Journal of Economic Sociology, 2010)
The end.The Beginning see in Т. 7. № 3.